Soil Fertility Assessment of Sugarcane Farms in Barangay Aglayan, Malaybalay, Bukidnon, Philippines - Ligan, Willy Aclon (Journal of Tropical Crop Science, 2016)
A soil fertility assessment survey was conducted at Barangay Aglayan, Malaybalay, Bukidnon, Philippines, on selected farms to assess the soil chemical properties (pH, OM, Extractable P and Exchangeable K) of sugarcane farms. A survey questionnaire was used to gather information among farms and a total of twenty-two (22) sugarcane farms were collected for soil samples and analyzed at the Soil and Plant Analysis Laboratory, College of Agriculture, Central Mindanao University. The 22 sugarcane farms surveyed in of Barangay Aglayan, Malaybalay, Bukidnon were identified as very strongly acidic, have medium organic matter content, low extractable phosphorus and very low in exchangeable potassium. These results demonstrated that the sugarcane farms in Bukidnon need amendments to meet the recommended soil test values for sugarcane. The results of this study have provided basic information to generate a soil nutrient map of sugarcane farms in Bukidnon, Philippines.